Application of Natural Zeolites in Anaerobic Digestion Processes: A Review - Montalvo-Martinez, S (ELSEVIER SCIENCE BV, 2012)
This paper reviews the most relevant uses and applications of zeolites in anaerobic digestion processes. The feasibility of using natural zeolites as support media for the immobilization of microorganisms in different high-rate reactor configurations (fixed bed, fluidized bed, etc.) is also reviewed. Zeolite, with its favorable characteristics for microorganism adhesion, has also been widely used as an ion exchanger for the removal of ammonium in anaerobic digestion due to the presence of Na+, Ca2+ and Mg2+ cations in its crystalline structure. This property is also useful for improving the anaerobic process performances in the treatment of wastewaters with high concentrations of nitrogen compounds, such as cattle, pig and chicken wastes, as it prevents process inhibition. The influence of zeolite particle size and doses in batch mesophilic and thermophilic processes when referring to synthetic or different wastewaters is also reviewed. Finally, the role of zeolite in granulation processes, in anaerobic oxidation processes (Anammox) for promoting the retention of the biomass involved (given its low growth rate), and in hybrid and sequencing reactors such as the moving bed biofilm reactors (MBBR) are also discussed. (C) 2012 Elsevier B.V. All rights reserved.